2013
DOI: 10.1021/bi3008609
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Controlled Assembly of Hexamers, Dihexamers, and Linear Multihexamer Structures by the Engineered Acylated Insulin Degludec

Abstract: Insulin degludec, an engineered acylated insulin, was recently reported to form a soluble depot after subcutaneous injection with a subsequent slow release of insulin and an ultralong glucose-lowering effect in excess of 40 h in humans. We describe the structure, ligand binding properties, and self-assemblies of insulin degludec using orthogonal structural methods. The protein fold adopted by insulin degludec is very similar to that of human insulin. Hexamers in the R(6) state similar to those of human insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 63 publications
7
75
1
4
Order By: Relevance
“…Upon diffusion of phenol following injection, the IDeg di-hexamers open at both ends and lead to the formation of multi-hexamers [16]. This mechanism is corroborated in an in vivo study in pigs, which has demonstrated that IDeg forms structures resembling the multi-hexamer formation of IDeg upon SC injection [17], and supporting in vitro observations [16] with electron microscopy [18] (Fig. 2).…”
Section: Mechanism Of Protraction Of Insulin Degludec (Ideg)supporting
confidence: 59%
See 1 more Smart Citation
“…Upon diffusion of phenol following injection, the IDeg di-hexamers open at both ends and lead to the formation of multi-hexamers [16]. This mechanism is corroborated in an in vivo study in pigs, which has demonstrated that IDeg forms structures resembling the multi-hexamer formation of IDeg upon SC injection [17], and supporting in vitro observations [16] with electron microscopy [18] (Fig. 2).…”
Section: Mechanism Of Protraction Of Insulin Degludec (Ideg)supporting
confidence: 59%
“…5, p. 2,112), with kind permission from Springer Science + Business Media). b A transmission electron microscope image showing the effect of phenol on IDeg multi-hexamer linkage—the figure depicts elongated IDeg structures in the absence of phenol; the scale bar represents 200 nm (adapted and reprinted with permission from Steensgaard et al [18]; Copyright 2014 American Chemical Society)…”
Section: Mechanism Of Protraction Of Insulin Degludec (Ideg)mentioning
confidence: 99%
“…The threonine amino acid residue at B30 is deleted and a fatty acid (hexadecanedioic acid) is added to the lysine at B29 via a glutamic acid spacer [1]. Following a subcutaneous injection, insulin degludec forms a depot of multihexamer chains and these multihexamers gradually disassemble into active monomers that are slowly absorbed into the circulation [2,3]. Therefore, there is stable release of insulin degludec from the subcutaneous depot, resulting in stable glucose lowering profile with a long duration of action (> 42 h) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Phase 3 studies comparing insulin glargine U300 and insulin glargine U100 showed similar reductions in the HbA1C levels, but the rate of severe hypoglycemia was 23% lower in the U300 arm. 95 Glargine U300 forms a compact subcutaneous depot with a small surface area upon injection, resulting in a more gradual, long-term, and flatter release than with standard glargine U100, enabling glucose control up to 36 hours. 90 Reduced cases of nocturnal hypoglycemia is like a clinical benefit provided by ultra-long pharmacokinetic profile of these novel analogues.…”
Section: High Dose Formulationsmentioning
confidence: 99%